(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Abstract: This scientific article describes cases of mixed diplococcosis and pasteurellosis infections in lambs, the dynamics of their spread, disease diagnostics, clinical signs, as well as methods of prevention and treatment Аннотация: В научной статье описаны заболеваемости диплококкозом у ягнят, динамика их распространения, патоморфология заболевания, клинические признаки, методы профилактики и лечения